Management of refractory hypoxemia during one-lung ventilation applying CPAP through a bronchial blocker to non-operated lobes on the operative side in combination with a double lumen tube: a case report - Conne, Pierre; Lutz, Jon Andri; Grandjean, Corinne; Maarbess, Rachelle; Al Chammas, Monique (Frontiers in Anesthesiology, 2026)
One-lung ventilation (OLV) is the standard treatment during thoracic surgery; however, maintaining adequate oxygenation can be particularly challenging in patients with a history of contralateral lobectomy. We report the case of a 44-year-old woman who underwent uniportal video-assisted thoracic surgery for a right upper lobectomy after a previous left upper lobectomy. The patient developed severe hypoxemia during OLV despite maximal ventilatory adjustments and the application of conventional continuous positive airway pressure (CPAP) to the operative lung, which impaired surgical exposure. As a rescue strategy, a bronchial blocker was advanced through a left-sided double-lumen tube (DLT) into the right bronchus intermedius, enabling selective delivery of CPAP to the right middle and lower lobes while maintaining collapse of the right upper lobe. This approach successfully restored oxygenation without interfering with the surgical field. This case illustrates that the combined use of a DLT and bronchial blocker can provide an effective and safe solution for refractory hypoxemia and can be considered as a rescue technique in complex thoracic procedures in patients with prior contralateral resections.